Startegi Pengelolaan Persampahan di Kecamatan Colomadu - Satyarsa Wienuri; Jawoto Sih Setyono (Jurusan Perencanaan Wilayah dan Kota, 2016)
Growing population have caused increasing waste production. Waste problem is not only faced by large cities, but small ones are going to be, one of them is Colomadu District. Colomadu separated geographically but still one of Karanganyar’s administrative region, this condition is called exclave. Exclave caused waste problems because high production did not pursued by carrying intensity. The research purpose is to make solid waste management strategy with two phase of plan making, research and planning. Research phase aims to identify existing problems with observation, questionnaire, and interview. Planning is purposed to make strategies that consist of process flow and activities in each process. Researcher involved society and government suggestions through depth interviews. There are four characteristics of waste management in Colomadu. Waste to Recource concept focus in adding mangement points.